Uncertainty, Wage Setting and Decision Making in a Monetary Union - Carsten Hefeker (Hamburg Institute of International Economics (HWWA), 2004)
The enlargement of the European Monetary Union is likely to lead to an increase of uncertainty about the transmission of monetary policy for the larger union. Adding new members to the central bank council will in addition imply that the preferences of the enlarged council will be uncertain in the initial period. The paper considers the influence of both types of uncertainty on wage setting behavior in the larger monetary union and its effects on unemployment. In light of these effects, implications for the adequate structure of the central bank are derived.
Keywords: E58; D72; 330; Monetary Policy Uncertainty; Wage Setting; European Central Bank; Euro Area; Accession Countries; Europäische Wirtschafts- und Währungsunion; EU-Erweiterung; Geldpolitik; Risiko; Glaubwürdigkeit; Lohnbildung; Transmissionsmechanismus; Arbeitslosigkeit; Theorie